Jurnal Pencegahan dan Penanganan Kekerasan Seksual menggunakan Natural Languange Process dan Data Science - Alissyah Putri; Dani Azka Faz; Anshari Rusmeniar R.A; Yuni nur fari'ah; Falah Arfani; Faisal Dharma Adhinata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Violence against women is something that is often heard and discussed in society. Women are often victims of discrimination, harassment and violence. Sexual harassment and violence in Indonesia is certainly not only experienced by adult women, but can also be experienced by children and adult men. Although in many cases it is more experienced by women. Of all respondents who were victims of sexual violence, almost all preferred or decided not to report the sexual violence and harassment they experienced. The cause is a psychological problem because of what happened to him, which makes him confused, embarrassed, afraid and even feels self-blame for what he experienced. This is the basis for the author to build a Chatbot and Recommendation System as a form of care and also a solution for victims of sexual violence by presenting a website